Metode Tafsir Putusan Mahkamah Konstitusi dalam Pengujian Konstitusional Undang-Undang Cipta Kerja - Dodi Haryono (Jurnal Konstitusi, 2021)
The use of the constitutional interpretation method by the judges of the Indonesian Constitutional Court (MK-RI) in their decision’s consideration (ratio decidendi) determine the decisions quality, therefore it must be chosen appropriately. In the context of Indonesian rule of law, the use of constitutional interpretation method should be implemented holistically, integrative, and using a dynamic approach, that must be harmonized with the Pancasila. This article is aimed to explain and analyze the use of constitutional interpretation method in the Constitutional Court Decision Number 91/PUU-XVIII/2020 regarding the Formal Constitutional Review of Law Number 11 of 2020 concerning Job Creation, as well as its theoretical implications. This article also proposes a new approach for constitutional interpretation method which is expected to strengthen the normative legitimacy and justification of the MK-RI decisions in the future. The method of analyses used in this article is the legal normative analyses with a conceptual approach. Finally, this article concludes that the method of constitutional interpretation in the Constitutional Court Decision Number 91/PUU-XVIII/2020 is considered as eclecticism. Using the new approach, the decision has also fulfilled the principles of holistic, integrative and dynamic constitutional interpretation based on Pancasila. For this reason, the Constitutional Court Decision Number 91/PUU-XVIII/2020 deserves to be used as one of the Landmark Decisions at the Indonesian Constitutional Court. However, the eclecticism approach wich is used by Indonesian Constitutional Court to interpret the constitution still needs to be developed in order to increase the normative of legitimacy and justification of decisions quality. In addition, that approach must also be linked to Pancasila both as a rechtsidee and staatsfundamentalnorm of the Indonesian state.